Antioxidant and antimicrobial preservatives: Properties, mechanism of action and applications in food – a review. Issue 11 (17th June 2022) - Bensid, Abdelkader; El Abed, Nariman; Houicher, Abderrahmane; Regenstein, Joe M.; Özogul, Fatih
Abstract: In the food industry, there is a need to use the properties of antioxidants and antimicrobials effectively to prevent microbial growth in foods, as well as to retard the oxidation of fats to delay rancidity. Nevertheless, the emerging concern about the negative effects of synthetic antioxidants and antimicrobials on consumers' health along with the advantages of natural substances have led to more fundamental research to investigate the mechanism of action and toxicity of natural antioxidants and antimicrobials. There is also a need to establish in each country an appropriate regulatory scheme to assure consumers of the safety and efficacy of these materials. Thus, this present review provides a detailed overview of the different antioxidant and antimicrobial groups, focusing on their properties, mechanism of action, and applicability in the food industry to be a guide for students and researchers.